Taurine effects on the occurrence of cardiac arrhythmias and QT interval dispersion in patients with postinfarction cardiosclerosis and chronic heart failure: a comparative randomised study - I. G. Gordeev; E. M. Pokrovskaya; E. E. Luchinkina (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To study the effects of taurine therapy on the occurrence of cardiac arrhythmias and QT interval dispersion (dQT) among patients with postinfarction cardiosclerosis (PICS) and subsequent chronic heart failure (CHF). Material and methods. The study included 40 patients with previous myocardial infarction (MI), left ventricular ejection fraction (LVEF) <45 %, and Functional Class (FC) II-III CHF (NYHA). The participants were randomised into two groups: the main group (MG) included 20 patients receiving standard CHF treatment and taurine, while the control group (CG; n=20) was administered standard CHF treatment only. Both groups were comparable by the main clinical and anamnestic parameters. The therapy phase lasted 3 months. The analysis of taurine effects on the occurrence of cardiac arrhythmias and dQT was performed in the subgroups defined according to the CHF FC. dQT was assessed by 12-lead electrocardiography (ECG), while the arrhythmia occurrence was assessed by Holter ECG monitoring. The examined parameters were measured at baseline and after 3 months of the therapy. Results. In PICS patients with CHF, taurine demonstrated beneficial effects on the dynamics of dQT and cardiac arrhythmia occurrence. Conclusion. Taurine could be included in the complex treatment of PICS patients with FC II-III CHF.